A skill acquisition based framework for aiding lower limb injury rehabilitation using a single inertial sensor with concurrent visual feedback - Shepherd, J. B.; Rowlands, D. D.; James, D. A. (Procedia Engineering, 2016)
Technology to aid the acquisition and performance of motor skills is becoming increasingly commonplace however there is distinct disconnect between these technological interventions and a detailed understanding of how to design technology to best instruct a learner. Using a single inertial sensor with bespoke concurrent visual feedback, based in a MATLAB data visualisation environment, this paper presents a skill acquisition framework to facilitate home based physiotherapy interventions. When athletes and patients are prescribed at home based physiotherapy interventions the current literature reports low rates of adherence. In addition the lack of monitoring and exercise classification raises concerns towards the quality of rehabilitation program outcomes. A trial was conducted randomly assigning twenty two uninjured participants to two categories, one with the aid of the rehabilitation software and the other a control group with no feedback. Both groups received the same visual instructions on the three simple leg static stretching tasks that are indicative of lower limb injury physiotherapy interventions. The results showed statically significant improvements in both the program adherence as well as the error mitigation of the feedback group in comparison to the control. Substantiating the skill acquisition framework errors for the feedback group seemed to lessen over time synonymous with an immediate learning effect as a result of the concurrent feedback. The findings suggest that at home physiotherapy interventions could be enhanced by using a concurrent biofeedback skill acquisition based single inertial sensor system. Evidently improving adherence, technique and allowing for the data to be accrued over time and relayed to practitioners and coaching staff ultimately giving them heightened confidence in monitoring physiotherapy progress. The wider implications means this research could be useful in tracking and providing feedback for a range of sports injury circumstances to ultimately improve the outcomes of the physiotherapy interventions.